Phase‐Reversal Emulsion Catalysis with CNT–TiO2 Nanohybrids for the Selective Oxidation of Benzyl Alcohol1. Issue 48 (7th November 2013) - Yu, Chang; Fan, Liman; Yang, Juan; Shan, Yuanyuan; Qiu, Jieshan
<x xml:space="preserve">Abstract</x> Mix it up: Carbon nanotube (CNT)–TiO2 nanohybrids with the potential to control the phase of an emulsion were successfully developed with a simple yet efficient method (see figure). When ruthenium was deposited on these CNT–TiO2 nanohybrid supports, they demonstrated catalytic potential for the selective oxidation of benzyl alcohol to benzaldehyde. The relationship between the emulsion properties and the catalytic mechanism is also discussed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>